2023
DOI: 10.3390/foods12030458
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Review on the Research Progress of Citric Acid Modified Starch

Abstract: Citric acid (CA) treatment is a convenient, mild and environmentally friendly strategy to modify the composition, structure and function of starch through hydrolysis and esterification, which expands the application of starch in industry. In this paper, the effects of CA modification on amylose content, amylopectin chain length distribution, microscopic morphology, solubility and swelling ability, thermodynamic properties, gelatinization properties, digestibility properties, texture properties and the film-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…45 In addition, free amylose chains leaching out of starch granules may form double helical assemblies that in turn increase the RC. 46…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 In addition, free amylose chains leaching out of starch granules may form double helical assemblies that in turn increase the RC. 46…”
Section: Resultsmentioning
confidence: 99%
“…45 In addition, free amylose chains leaching out of starch granules may form double helical assemblies that in turn increase the RC. 46 Further analysis of the thermal properties of the samples by DSC (Table 1) revealed that the treated ARS samples displayed significant increases in T o , T p , and T c and a decrease in ΔH compared to the native ARS. Such differences in starch properties can be attributed to the interplay of three factors: (i) the molecular structure of amylopectin (unit chain length, extent of branching) (ii) starch composition (amylose to amylopectin ratio, amount of lipid complexed, amylose chains, phosphorus content), and (iii) granular architecture (crystalline to amorphous ratio).…”
Section: Food and Function Papermentioning
confidence: 99%
“…Among these methods, starch hydrolyzation by adding an acid such as citric acid is widely used for food starch because it increases paste viscosity and preserves paste properties and texture during cold storage [16][17][18]. Citric acid is a natural organic acid with a multicarboxylic structure, which makes it useful as a starch crosslinking agent [19,20]. It is non-toxic, highly soluble, and has antioxidant and mild reaction properties.…”
Section: Introductionmentioning
confidence: 99%
“…Citric acid can modify the composition, structure, and function of starch through hydrolysis and esterification. This largely depends on factors such as temperature, concentration, processing time, and the ratio of amylose to amylopectin in the starch [19,20]. It has been shown to affect the physical and chemical properties, paste texture, structure, thermal behavior, rheology, and digestibility of talipot palm starch, causing a decrease in relative crystallinity from 16.35 to 3.06% [19].…”
Section: Introductionmentioning
confidence: 99%
“…This resistance may have potential implications in the developing of new starch-based products with improved functionalities. Also, the use of treatment with organic acids may cause the breakage of some branches of amylopectin, which increases the straight unbranched chains, which helps to form crystals containing helix chains that are resistant to amylase enzymes [40] . Although these mechanisms have a mutual effect, the response of starch types is different depending on their crystalline structure, which is the aim of this current work.…”
Section: Introductionmentioning
confidence: 99%